1997
DOI: 10.1021/ic960932x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure ofN,N-Dimethylthioformamide Solvates of the Divalent Group 12 Ions with Linear Coordination Geometry for Mercury(II), Tetrahedral for Zinc(II), and Octahedral for Cadmium(II)

Abstract: The crystalline solvates of the divalent group 12 metal ions with the soft sulfur donor N,N-dimethylthioformamide display an unusual variation in coordination number and geometry with two, four, and six ligands attached to the mercury(II), zinc(II), and cadmium(II), ions, respectively. Bis(N,N-dimethylthioformamide)mercury(II) perchlorate precipitates from acetonitrile solution when adding less than 2 equiv of N,N-dimethylthioformamide, while the zinc and cadmium solvates crystallize from saturated N,N-dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 36 publications
3
49
1
1
Order By: Relevance
“…[10][11][15][16] Thus, the Hg(1)-S(2) interaction is consistent with strong coordination to the Hg II center, whereas the Hg (1) [3] Perchlorate coordination to Hg II has been observed in several previously reported complexes. [4,[17][18][19][20][21] In these, the Hg II -O(perchlorate) bond lengths generally range from 2.66-2.95 Å. Notably, one of these reported structures has Hg II -S(thioether) bonding as well as a weakly coordinated perchlorate (Hg-O, 3.08 Å) in a sixth coordination position.…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…[10][11][15][16] Thus, the Hg(1)-S(2) interaction is consistent with strong coordination to the Hg II center, whereas the Hg (1) [3] Perchlorate coordination to Hg II has been observed in several previously reported complexes. [4,[17][18][19][20][21] In these, the Hg II -O(perchlorate) bond lengths generally range from 2.66-2.95 Å. Notably, one of these reported structures has Hg II -S(thioether) bonding as well as a weakly coordinated perchlorate (Hg-O, 3.08 Å) in a sixth coordination position.…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…[9,10] Di-and tridentate sulfur-donor ligands are required to form six-coordinated mercury(II) complexes. [11][12][13] The destabilization of regular six-coordinated mercury(II) complexes, including small monodentate ligands, such as ammonia, is often attributed to a contribution of the mercury(II) 5d z 2 atomic orbital to the bonding molecular orbitals by vibronic coupling of pseudo-degenerate electronic states in a socalled pseudo-Jahn-Teller effect (PJTE).…”
Section: Introductionmentioning
confidence: 99%
“…No evidence of disordering or large vibrational movements was found for the perchlorate ions in spite of the absence of hydrogen bonds. The perchlorate ion is located on the three-fold axis, with one Cl À O bond along the axis, 1.4366 (13) , and three equivalent symmetry related Cl À O bonds of 1.4447 (9) . The average Cl À O distance of 1.442 does not vary significantly from the values found in weakly hydrogen-bonded perchlorates, 1.41-1.44 , as observed for a large number of compounds.…”
mentioning
confidence: 99%
“…1). It has been reported that the complexes of Hg(II) with N-(substitutedphenyl)thiobenzamide [7] and N,N-dimethylthioformamide [8] are due to sulfur donation. In the IR spectrum of Hg(II)-sorbed PTA1, a higher frequency shift of (C-N) for the thioamide group (1539 cm −1 ) was observed (1490 cm −1 for PTA1 before the sorption), indicating the sulfur-coordination of the thioamide group and an increase in double bond character of the C-N bond in the coordination form [7,16].…”
Section: Sorption Behavior Of Hg(ii) On Powdered Ptamentioning
confidence: 99%
“…It is known that Hg(II) forms a stable complex with thioamide ligand [7,8]. However, to our knowledge, only a few reports have been appeared for the polymer sorbents having thioamide group for Hg(II) [9,10].…”
Section: Introductionmentioning
confidence: 99%